EXPERIMENTAL AND NUMERICAL ANALYSES OF A HEAT PUMP-DRIVEN CHILLED CEILING SYSTEMS - (:unkn) unknown (BEGELL HOUSE INC, 2018)
Passive cooling covers the natural processes of heat dissipation and heat gain operations and provides a highly efficient, comfortable environment around. As commonly known, when air is heated, it rises, when cooled, it descends. Natural cooling and heating use this physical property of air to provide the best thermal conditions. In this study, an air-to-water heat pump system used for chilled ceiling operations was analyzed numerically and experimentally. Main objective of this study is to obtain COP of the heat pump system. In order to determine the efficiency, test room was established with heat pump-driven passive chilled ceiling panels. The test room was constructed of 120-mm polyurethane panels to minimize heat losses. All the data obtained from the system is recorded on a time period of per-second based during the processes.
Keywords: chilled ceiling; heat pump; cooling; THERMAL COMFORT